(untitled) (Molecular Medicine Communications, 2022)
T cells play important roles in combating various diseases, including cancers. To find out what genes hinder the function of T cells, Freitas and colleagues performed genome-wide CRISPR knock-out experiments in human chimeric antigen receptor T cells. They found that two genes, MED12 and CCNC, which are part of the Mediator kinase module, had the most significant effect. They discovered that antitumor activity was increased when MED12 was selectively deleted, and the effector phenotype was maintained in chimeric antigen receptor and T cell receptor-engineered T cells. They found increased occupancy of core Mediator chromatin at transcriptionally active enhancers in MED12-deficient cells. This effect was most evident for enhanced IL2RA expression and STAT and AP-1 transcription factors. The authors concluded that Mediator plays a vital role in T cell effector programming and that antitumor T cell response may be enhanced by targeting the Mediator kinase module. Science (2022). DOI: 10.1126/science.abn5647.